Are More Competitive Banking Systems More Stable? - Cihak, Martin (IMF Working Papers; Working Paper ;, 2006)
This paper provides the first empirical analysis of the cross-country relationship between a direct measure of competitive conduct of financial institutions and banking system fragility. Using the Panzar and Rosse H-Statistic as a measure for competition in 38 countries during 1980-2003, we present evidence that more competitive banking systems are less prone to systemic crises and that time to crisis is longer in a competitive environment. Our results hold when concentration and the regulatory environment are controlled for and are robust to different methodologies, different sampling periods, and alternative samples.